Assessment of a Natural Phytobiotic Mixture as Feed Additive for Broiler Chicken: Studies on Animal Performance, Gut Health, and Antioxidant Status After Experimental Infection with Eimeria spp. - Dimitrios Galamatis; Ioannis Panitsidis; Tilemachos Mantzios; Georgios Sioutas; Ioanna Stylianaki; Elias Papadopoulos; Jog Raj; Marko Vasiljević; Jasna Bošnjak-Neumüller; Damer Blake; Vasilios Tsiouris; Ilias Giannenas (Poultry)
This study evaluated the effectiveness of phytobiotic supplementation in managing coccidiosis in broiler chickens, a disease that impacts productivity. Three hundred sixty Ross-308 one-day-old chicks were assigned to five treatment groups: control negative (CN), phyto negative (PN), control infected (CI), phyto infected (PI), and salinomycin infected (SI). All diets were fed for the entire experiment duration. CN and CI groups were given a common diet, with CN remaining uninfected and CI exposed to Eimeria spp., while PN and PI groups received a phytobiotic supplement containing essential oils, saponins, and tannins (with PI challenged by Eimeria spp.), and SI received salinomycin post-infection. All infected groups were challenged on day 14 with Eimeria acervulina, E. maxima, and E. tenella. By day 21, PN had the highest body weight (744.9 g). Body weight gain (BWG) was highest in CN and PN from days 14–35, while CI consistently showed the lowest BWG. PI demonstrated significantly lower oocyst counts than CI, outperforming even SI by day 7, and showed milder intestinal lesions. A high anticoccidial index (ACI) of 188.45 was observed in PI, close to uninfected groups, while SI achieved a partially effective ACI of 136.91. Overall, PN and PI exhibited improved performance and intestinal health, highlighting the potential of phytobiotics in coccidiosis management for broilers.